Love on location - Carter, Cassidy (Hallmark Publishing, 2018)
"Delaney Phillips, a divorced mom, works for her longtime best friend Wyatt Andrews at Cabins in the Pines. Wyatt inherited the rustic resort from his father, and both he and Delaney have made countless happy memories there. After a highway bypass leaves it a little too off the beaten path, they'll do just about anything to keep it open. At Delaney's urging, Wyatt auditions for a reality TV program that helps businesses in trouble. The show's glamorous host arrives with her camera crew, turning the place upside down in hilarious and alarming ways. But Delaney doesn't like the woman's new plans for the business ... or her designs on Wyatt. Because even though Delaney's known him since the first grade, she's slowly but surely falling in love with him. Can she help him see the cabins - and their relationship - in a different light?"--Amazon.com